2016
DOI: 10.1016/j.rbr.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Infecção sistêmica e localizada por Candida spp. em pacientes reumatológicos em terapia anti‐TNF

Abstract: This was the first study to assess the prevalence of invasive and localized fungal disease by candida in a significant number of patients with rheumatic diseases on anti-TNF therapy, and demonstrated low risk of candidiasis, despite the high prevalence of immunosuppressive drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“… 10 , 21 To the contrary, Aikawa et al found a very low prevalence of Candida in patients with rheumatic diseases who received anti‐TNF‐therapy. 14 In their study, only one out of 194 patients (0.5%) had Candida , and none of them experienced systemic candidosis. 14 Interestingly, the authors only evaluated cases with symptomatic infection among women with autoimmune disorders, while all women in our study were asymptomatic at the time of screening.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 10 , 21 To the contrary, Aikawa et al found a very low prevalence of Candida in patients with rheumatic diseases who received anti‐TNF‐therapy. 14 In their study, only one out of 194 patients (0.5%) had Candida , and none of them experienced systemic candidosis. 14 Interestingly, the authors only evaluated cases with symptomatic infection among women with autoimmune disorders, while all women in our study were asymptomatic at the time of screening.…”
Section: Discussionmentioning
confidence: 91%
“…Only, a few studies have investigated their vaginal microbiota; some have reported a link between immunosuppression, autoimmune disease and vaginal infections, 10 , 11 , 12 , 13 and others have demonstrated contradictory results. 14 However, no data yet exist about the incidence of vaginal infections in rheumatic patients during pregnancy. In order to avoid infection‐related complications and prevent an accumulation of risk factors for PTB, it is indeed important to further evaluate the comparative risk of an abnormal vaginal microbiota that could lead to vaginal infections in these women.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos epidemiológicos têm demonstrado um aumento considerável de candidíase em pacientes imunodeprimidos, como também apresentam alto índice de mortalidade nas sepses nosocomiais. (AIKAWA et al, 2016) Além disso, a candidíase sistêmica afeta principalmente pacientes submetidos às drogas imunossupressoras, incluindo glicocorticoides, antibioticoterapia de amplo espectro e procedimentos invasivos. As infecções sistêmicas por Candida spp.…”
Section: Introductionunclassified